Pengaruh Audit Tenure dan Profitabilitas Terhadap Audit Delay (Studi Empiris pada Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024) - Yopi Stevani; Indupurnahayu .; M. Anwar Masruri (CV. ITTC INDONESIA, 2026)
Delays in publishing audited annual financial statements (audit delay) remain a crucial barrier to transparency for consumer non-cyclicals companies listed on the Indonesia Stock Exchange, particularly during the economic recovery phase of 2021-2024. Companies frequently miss the Financial Services Authority's (OJK) 90-day submission deadline, risking administrative sanctions. This study aims to empirically examine and analyze the partial and simultaneous effects of audit tenure and profitability on audit delay. A quantitative approach with causal associative explanatory research design was deployed. The research population comprised all consumer non-cyclicals sub-sector companies listed on the IDX during 2021–2024. Using a purposive sampling technique, a final sample of 53 companies was selected, yielding 212 observations over 4 years. Secondary data was gathered using documentation methods from audited financial reports on the official IDX website. The data analysis technique utilized panel data regression with the Random Effect Model (REM) estimation, processed via E-Views 14 software. The results demonstrate that partially, audit tenure has a negative and significant effect on audit delay (p = 0.0000), indicating that longer engagements with public accounting firms enhance audit efficiency. Conversely, profitability measured by Return on Assets (ROA) shows no significant partial effect on audit delay (p = 0.9898). Simultaneously, the F-test indicates that both audit tenure and profitability significantly influence audit delay (p = 0.0000), explaining 12.88% of the variance as indicated by the Adjusted R-squared. The study concludes that the auditor's familiarity and deep understanding of the client's business operations serve as the dominant factor in reducing financial reporting delays. The practical implication suggests that companies should maintain stable professional relations with audit firms within regulatory rotation limits, while continuously improving internal control systems to ensure effective monitoring of agents by principals.